การวิเคราะห์ความคิดเห็นของผู้ปกครองที่มีต่อการสื่อสารกับครูอนุบาลผ่านเครือข่ายสังคมออนไลน์ ในโรงเรียนสาธิตมหาวิทยาลัยศิลปากร (ปฐมวัยและประถมศึกษา) - แก้วลี, ณัฎฐา; เหมชะญาติ, วรวรรณ (An Online Journal of Education, 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อวิเคราะห์ความคิดเห็นของผู้ปกครองที่มีต่อการสื่อสารกับครูอนุบาลผ่านเครือข่ายสังคมออนไลน์ในโรงเรียนสาธิตมหาวิทยาลัยศิลปากร (ปฐมวัยและประถมศึกษา) ในด้านการใช้เฟสบุ๊ก และด้านการใช้ไลน์ ตัวอย่างประชากรคือ ผู้ปกครองเด็กระดับชั้นอนุบาลที่กำลังศึกษาในภาคการศึกษาปลาย ปีการศึกษา 2557 จำนวน 108 คน เครื่องมือที่ใช้ในการวิจัยคือ แบบสอบถาม วิเคราะห์ข้อมูลโดยการแจกแจงความถี่ หาค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า ความคิดเห็นของผู้ปกครองที่มีต่อการสื่อสารกับครูอนุบาลผ่านเครือข่ายสังคมออนไลน์โดยภาพรวมอยู่ในระดับดี โดยมีรายละเอียดในแต่ละด้านคือ (1) ด้านการใช้ไลน์ รายการที่มีค่าเฉลี่ยสูงสุดคือ การสนับสนุนการจัดการเรียนรู้ของครู ได้แก่ การให้คำแนะนำหรือแจ้งเตือนข้อมูลเกี่ยวกับการบ้านและใบงาน การให้กำลังใจเกี่ยวกับการจัดการเรียนการสอนของครู (2) ด้านการใช้เฟสบุ๊ก รายการที่มีค่าเฉลี่ยสูงสุดคือ การจัดการเรียนรู้ของครู ได้แก่ การให้คำแนะนำเพื่อเตรียมความพร้อมของบุตรหลานก่อนเปิดเทอม การนำเสนอข้อมูล ภาพถ่ายหรือคลิปเกี่ยวกับกิจกรรมที่พัฒนาเด็กทั้ง 4 ด้าน The purpose of this research was to analyze parents’ opinions towards communication vs social network in the Demonstration School of Silpakorn University (Kindergarten and Elementary) in 2 aspects: using facebook, and using line. The sample group was 108 parents of preschooler studying in the second semester of the 2014 academic year. The research instrument was a questionnaire form. The data were analyzed by using frequency, means, and standard deviation. The research findings found that overall of the parents’ opinions towards communication vs social network was at the level of well performed. Each aspect, having the highest means, was described as follow: (1) using line: supporting teachers’ learning provision such as giving advice or warning information about children’ homework or worksheets, and encouraging teachers’ learning provision, and (2) using facebook: organizing teachers’ learning such as a suggestion of children’ readiness before the school begins, and posing information or activities clips concerning with four dimensions of children development. 24) at the most, followed is Planning preparation (PNImodified = 0.17) and (3) The strategies for preschool teachers development in organizing free play activities is learning and applying in organizing free play activities, Implementation followed preparing lesson plan, creating a classroom atmosphere conducive to good behavior, getting to know each child, observant to children development, practicing self reflection and children's behavior, coordination with administrators and parents. Except potential for development. Teachers also need the cooperation of those involved administrator and education officer.